LEGAL PROTECTION OF INTERIOR DESIGN IN INDUSTRIAL DESIGN INTELLECTUAL PROPERTY RIGHTS - Ida Ayu Sadnyini; I Gede Putu Agus Wistama Putra; A.A.A.Ngurah Sri Rahayu Gorda; A.A.A. Ngurah Tini Rusmini Gorda (NOTARIIL Jurnal Kenotariatan, 2021)
Intellectual property is creativity that results from human thought in order to meet the needs and welfare of human life. Currently, IPR issues are widely discussed in the context of international issues. IPR includes two parts, namely Copyrights and Industrial Property Rights. Industrial property rights include patents, industrial designs, integrated circuits layout designs, trade secrets, geographic indications, trademarks and plant variety protection (PVP). Interior design is part of industrial design. Interior design has experienced significant developments in recent years, including in Indonesia. Problems that arises is plagiarisms done by imitating or using the "similarity" of an interior design that already has an industrial design certificate without any permission from the design owner. This study aims to find out the legal protection of interior design in the intellectual property rights of industrial design and the legal basis used by judges in deciding industrial design rights disputes. The result of this study showed that the legal protection of interior design in the intellectual property rights of industrial design involved two legal protections; they are preventive legal protections and repressive legal protections. Furthermore, Gustav Radbruch's theory of legal ideals is used as a legal basis in deciding cases of disputes over industrial design rights based on justice, benefits, and legal certainty in the case of industrial design disputes Ecosfera Room.